Sustainable mobility indicators based on micro-scale urban form: the case of Monterrey City, Mexico - Castro Sánchez, Laura Elena; Delgado Ramos, Gian Carlo (Frontiers in Sustainable Cities, 2025)
Scientific literature has explored the potential of urban planning and design to contain sprawl and its impacts. However, the potential of public spaces to enhance active mobility at the proximity scale remains underexplored in the Global South. Discouraging automobile use compels addressing the nexus between urban morphology and public spaces vitality, extending beyond areas with proximity to public transport. We developed and applied a novel assessing tool to comprehend micro-scale morphological characteristics favoring walking and cycling in two polygons of Monterrey. By using a set of urban design and active mobility indicators, and considering prevalent mainstream practices and their social representations, we evaluate the feasibility to transform such polygons through fine-grained urban design. The SUFi model provides an initial framework within the context of ongoing research. This article presents preliminary findings that inform prospective research trajectories by identifying key limitations and opportunities in the development and application of indicators designed to ensure the study’s representativeness and enhance its replicability. Our findings suggest that urban areas developed during the “Mexican miracle” have greater short-term transformative potential compared to those established under a neoliberal urban model, highlighting the need for further exploration of action strategies for the latter.